Metazoan Hsp70 machines use Hsp110 to power protein disaggregation - Rampelt, Heike; Nillegoda, Nadinath B.; Scholz, Sebastian Richard; Bukau, Bernd (The EMBO journal, 2012)
Accumulation of aggregation‐prone misfolded proteins disrupts normal cellular function and promotes ageing and disease. Bacteria, fungi and plants counteract this by solubilizing and refolding aggregated proteins via a powerful cytosolic ATP‐dependent bichaperone system, comprising the AAA+ disaggregase Hsp100 and the Hsp70‐Hsp40 system. Metazoa, however, lack Hsp100 disaggregases. We show that instead the Hsp110 member of the Hsp70 superfamily remodels the human Hsp70‐Hsp40 system to efficiently disaggregate and refold aggregates of heat and chemically denatured proteins in vitro and in cell extracts. This Hsp110 effect relies on nucleotide exchange, not on ATPase activity, implying ATP‐driven chaperoning is not required. Knock‐down of nematode Caenorhabditis elegans Hsp110, but not an unrelated nucleotide exchange factor, compromises dissolution of heat‐induced protein aggregates and severely shortens lifespan after heat shock. We conclude that in metazoa, Hsp70‐Hsp40 powered by Hsp110 nucleotide exchange represents the crucial disaggregation machinery that reestablishes protein homeostasis to counteract protein unfolding stress.